Adaptação transcultural e análise das propriedades psicométricas do instrumento de Autoavaliação do Funcionamento Ocupacional (SAOF) para LIBRAS - ANDRADE, Luana Foroni (2020)
In the scientific field, there is a gap of methodological studies aiming to translate and adapt health instruments for the deaf population. The search for reliable data in the research field should lead researchers to reflect on possible biases and distortions when deaf people are not approached in surveys with instruments adapted to their cultural linguistic needs. Translated and adapted instruments can generate real data on the urgent demands of this population, in addition to offering equitable health care initiatives with reliable and valid instruments, positively influencing the economic and social aspects for individuals and governments. Assessing occupational functioning is fundamental in the perspective of understanding how these people perceive themselves able to perform their activities and their roles in different environments. This research aimed to analyze the psychometric properties of cross-cultural adaptation, and validity and reliability of the Self-Assessment of Occupational Functioning for Brazilian Sign Language. The study had two stages. In the first, an integrative literature review was carried out to identify recommendations for cross-cultural adaptation and validation of sign language instruments. In the second stage, a methodological research was carried out, which translated into Brazilian Sign Language and adapted the Self-Assessment of Occupational Functioning for the deaf population. For validation, the instrument was applied to a sample of 121 deaf people, through dissemination and contact by social networks in the national territory. Face and content validations, construct validation by known groups, and retesting were performed to assess the reliability of the instrument. The results of the first step showed the absence of a standard protocol for cross-cultural adaptation in sign languages, and a model based on evidence of cross-cultural adaptation and validation of Brazilian Sign Language instruments in Brazil was developed. In the second stage, the results indicated that the version of the instrument for Brazilian Sign Language was valid, reliable and replicable, with good internal consistency. The use of a valid and reliable instrument can help professionals with more efficient therapeutic propositions, increasing social participation and offering the opportunity to fully exercise citizenship. For the academic environment, methodological studies such as this one, allow the exchange of knowledge and paths among researchers in the field.